Active control strategy for switched systems against asynchronous DoS attacks - Zhao, Rui (2023)
This paper is dedicated to the switched systems suffering asynchronous denial-of-service (DoS) attacks that compromise sensor–controller and controller–actuator channels independently. By taking into account the energy constraints, the duration of DoS attacks has different maximum bounds for different channels. To eliminate the negative effect of DoS attacks, an active control strategy consisting of a predictor mechanism and a buffer mechanism is devised. In such a strategy, the controller sends a sequence of control signals to the actuator to guarantee the system energy does not increase too fast, even if the sensor–controller and the controller–actuator channels are attacked simultaneously. Furthermore, the mismatch of the controller and the subsystem is addressed due to the presence of event-triggered scheme and DoS attacks. It is shown that the systems’ states allow a bounded divergency over mismatched interval. To this end, the switching signal is designed in connection with the properties of DoS attacks, event-triggered scheme and system parameters. Finally, an example is carried out to verify the effectiveness of the theoretical results.